Artificial intelligence in the hotel industry in Slovakia - Gáll, Jozef (Hotel and Tourism Management, 2023)
Artificial intelligence in the hotel industry streamlines processes, personalizes services, enhances customer service, and analyzes data. It helps reduce costs, increase security, and improve competitiveness. In the current technology-driven era, it is essential for efficient operations and customer satisfaction. The main goal of the presented article is to explore and analyze the application of artificial intelligence in the hotel industry and map the effects it brings to hotels and other accommodation facilities in Slovakia. Using a sociological survey method in the form of a questionnaire, this article analyzes the extent of artificial intelligence technology implementation in accommodation facilities in Slovakia and the effects it brings. Based on the results of our primary research, we can conclude that artificial intelligence is not widely adopted in the Slovak hotel industry to its full potential, considering its possibilities and utilization in various operational areas of accommodation facilities.